2016
DOI: 10.1007/s00395-016-0596-8
|View full text |Cite
|
Sign up to set email alerts
|

Calpain 1 cleaves and inactivates prostacyclin synthase in mesenteric arteries from diabetic mice

Abstract: Diabetes is associated with a number of co-morbidities including an increased risk of developing cardiovascular diseases. The activation of Ca-activated proteases of the calpain family has been implicated in platelet activation associated with diabetes and this study aimed to determine the role of calpain activation in the development of endothelial dysfunction. Diabetes induction in mice attenuated acetylcholine-induced relaxation of mesenteric artery rings, an effect prevented in mice receiving a calpain inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…Melatonin activates the AMPK/PGCα1 pathway to preserve mitochondrial function and structure in vitro. Besides mitochondrial apoptosis, mitochondrial function and structure are essential for cellular viability (10,50). The primary function of mitochondria is to supply sufficient energy for cellular metabolism.…”
Section: Melatonin Suppresses Mitochondrial Apoptosis Via the Ampk/pgmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin activates the AMPK/PGCα1 pathway to preserve mitochondrial function and structure in vitro. Besides mitochondrial apoptosis, mitochondrial function and structure are essential for cellular viability (10,50). The primary function of mitochondria is to supply sufficient energy for cellular metabolism.…”
Section: Melatonin Suppresses Mitochondrial Apoptosis Via the Ampk/pgmentioning
confidence: 99%
“…Recently, several studies have documented the involvement of melatonin in kidney protection (9). Melatonin presumably enters mitochondria through melatonin receptor-dependent and -independent manners (10,11). Measurement of the sub-cellular distribution of melatonin revealed that the concentration of melatonin in mitochondria greatly exceeds that in blood (12), thus suggesting that melatonin may specifically target mitochondria.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of inflammation factors such as TNFα, MCP-1 and IL-6 were determined via ELISA (Cusabio Technology, Wuhan, China). The renal function was measured via analysing the levels of creatinine and blood urea nitrogen (BUN) using a Cobas® C311 Autoanalyzer (Roche Diagnostics, Indianapolis, USA) as per the manufacturer's protocols [26].…”
Section: Measurement Of Metabolic Parametersmentioning
confidence: 99%
“…In response to mitochondrial fission, mitochondria could employ lysosomes via Parkin to degrade damaged mitochondria and maintain a healthy mitochondrial population, which is essential for cell survival [18][19][20]. Notably, the impairment of Parkin-mediated mitophagy is a feature of DN, and various pharmacological activators of mitophagy have been shown to protect against glomerulosclerosis and proteinuria, renal hypertrophy, and mesangial expansion in rodent DN models [21][22][23]. However, the regulatory signaling upstream of mitophagy is far from clear.…”
Section: Introductionmentioning
confidence: 99%